Effects of brown seaweed polyphenols, α‐tocopherol, and ascorbic acid on protein oxidation and textural properties of fish mince (Pagrosomus major) during frozen storage. (1st July 2016) - Wang, Tiantian; Li, Zhenxing; Yuan, Fangzhou; Lin, Hong; Pavase, Tushar Ramesh
Abstract: BACKGROUND: Frozen storage of minced fish is currently one of the most important techniques to maintain its functional properties. However, some deterioration does occur during frozen storage and cause quality loss. The effects of brown seaweed polyphenols, α ‐tocopherol, and ascorbic acid on lipid and protein oxidation and textural properties of red sea bream ( Pagrosomus major ) during 90 days of frozen storage at −18 °C were investigated. RESULTS: All added antioxidants at 1 g kg −1 resulted in significantly lower thiobarbituric acid‐reactive substances (TBARS) compared to the control during the 45 days of frozen storage. The antioxidants were also effective in retarding protein oxidation concerning to total sulfhydryl content and protein carbonyl content. Brown seaweed polyphenols and α ‐tocopherol significantly retarded the inactivation of Ca 2+ ‐ATPase activity during the first 45 days, whereas ascorbic acid had no such effect. The antioxidant activity showed either an invariable or decrease trend after 45 days storage. Adding antioxidants had a significant effect on the breaking force of the gels during the frozen storage period. CONCLUSION: These results indicate that brown seaweed polyphenols and α ‐tocopherol can be used to prevent oxidative reactions and thus maintain the structure of the gel formed by fish mince during frozen storage. © 2016 Society of Chemical Industry